Exploring Multivalent Protein-Glycosensitizer Interaction with Phenalenone Derivatives in Mixed Micelles - Silva-Molina, C; Silva-Molina, C; Sandoval-Altamirano, C (Elsevier B.V., 2023)
Carbohydrates are involved in several biological processes, and they have been widely used in several technological applications. Carbohydrate-based surfactants have low toxicity, and they are environmental friendly, however, their physicochemical properties restrict their use in potential applications. Mixed micelles are an attractive model system to use for carbohydrate–based surfactants since their physical properties may be easily modulated with simple changes in the surfactants mixture ratio. In this study, we design a mixed micelle system composed by new synthesized glycolipids bearing a photosensitizer in their hydrophobic moiety. We hypothesize that this system would have two main functions a) singlet oxygen generation and b) multivalent capability to interact with lectins. These combined capabilities will permit the generation of the short-lived excited oxygen neighboring the targets to be oxidized. In this design, non-ionic mixed micelles were used to modify the interfacial properties and to improve the solubility in water of the synthesized glycosensitizers. In summary, our results show that both glycolipids retain their capability to generate singlet oxygen in homogeneous media and the mixed micelles behave as an adequate multivalent system to interact with Con A. We provide a promising system to be successfully employed in antibacterial photodynamic therapy. © 2023 Elsevier B.V.